Artificial Light Regulation of an Allosteric Bienzyme Complex by a Photosensitive Ligand. (4th July 2018) - Kneuttinger, Andrea C.; Winter, Martin; Simeth, Nadja A.; Heyn, Kristina; Merkl, Rainer; König, Burkhard; Sterner, Reinhard
Abstract: The artificial regulation of proteins by light is an emerging subdiscipline of synthetic biology. Here, we used this concept to photocontrol both catalysis and allostery within the heterodimeric enzyme complex imidazole glycerol phosphate synthase (ImGP‐S). ImGP‐S consists of the cyclase subunit HisF and the glutaminase subunit HisH, which is allosterically stimulated by substrate binding to HisF. We show that a light‐sensitive diarylethene (1, 2‐dithienylethene, DTE)‐based competitive inhibitor in its ring‐open state binds with low micromolar affinity to the cyclase subunit and displaces its substrate from the active site. As a consequence, catalysis by HisF and allosteric stimulation of HisH are impaired. Following UV‐light irradiation, the DTE ligand adopts its ring‐closed state and loses affinity for HisF, restoring activity and allostery. Our approach allows for the switching of ImGP‐S activity and allostery during catalysis and appears to be generally applicable for the light regulation of other multienzyme complexes. Abstract : Photocontrol of function in a bienzyme complex : Light‐sensitive 1, 2‐dithienylethene (DTE) ligands are used to control both catalysis and allostery within the imidazole glycerol phosphate synthase (HisF–HisH complex). Upon irradiation, the DTE ligand diffuses from the active site of HisF, allowing for substrate binding and concomitant activation of HisH.